Who is saving our streamflow data? Exploring volunteer profiles and their engagement in the SIREN data rescue project - Paola Mazzoglio; Miriam Bertola; Tommaso Listo; Luca Princivalle; Luca Lombardo; Alberto Viglione; Pierluigi Claps; Alvise Mattozzi (PLoS ONE, 2025)
SIREN is a citizen science project that involves lay people in the digitization of historical daily discharge measurements from Italian rivers. Such data, largely available only in printed yearbooks, hinders scientific progress in hydrological studies and water resource management. In this article, we examine the motivations behind citizen engagement in SIREN. Our multi-step approach combines quantitative analysis of online contributions, pilot interviews with selected volunteers, and a comprehensive questionnaire collecting basic demographic data and subjective impressions of the experience. Through these approaches, we identify three participant profiles: two driven primarily by the activity itself and one by the scientific content. The first profile values the straightforward nature of data entry, seeing it as an easy way to contribute with existing skills. The second profile treats participation as a leisure activity, readily fitting into brief intervals of free time. The third profile stems from deeper engagement, encompassing volunteers with professional or personal interests in hydrology, Italian geography, or both. The study also highlights the significant role of retired individuals (an underrepresented group in the citizen science literature) who often contribute using skills developed during their careers. This work highlights the importance of creating citizen science projects that are accessible, meaningful, and connected to volunteers’ lives and interests.